2018
DOI: 10.3991/ijim.v12i3.8713
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Teaching Mathematical Problems Solving Through Using Mobile Learning on the Seventh Grade Students' Ability to Solve them in Jordan

Abstract: <p><em>The study aimed to probe the effect of solving mathematical problems through using Mobile Learning (ML) on the seventh grade students' ability to solve them in Jordan. The study sample consisted of fifty-four (54) students of seventh basic grade in Zarqa in Jordan who were divided into two groups randomly: experimental group which included twenty-six (26) students who were taught through using mobile learning methodology and control group which consisted of twenty-eight (28) students who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 4 publications
0
11
0
2
Order By: Relevance
“…Thanks to this mobility and connectivity, students are able to learn more easily, practically, and productively (Choon-Keong, Ing, & Kean-Wah, 2013;Gikas & Grant, 2013). When accompanied with proper learning strategies, m-learning is also praised for its positive impact on students' learning achievement (Hwang & Chang, 2011;Hwang & Wu, 2014), attitudes towards the lesson (Hwang & Chang, 2011), interest and motivation (Hwang & Chang, 2011;Hwang & Wu, 2014), as well as on problem-solving skills (Al-Khateeb, 2018;Lai & Hwang, 2014), creativity, and communication skills (Lai & Hwang, 2014).…”
Section: Benefits and Barriersmentioning
confidence: 99%
“…Thanks to this mobility and connectivity, students are able to learn more easily, practically, and productively (Choon-Keong, Ing, & Kean-Wah, 2013;Gikas & Grant, 2013). When accompanied with proper learning strategies, m-learning is also praised for its positive impact on students' learning achievement (Hwang & Chang, 2011;Hwang & Wu, 2014), attitudes towards the lesson (Hwang & Chang, 2011), interest and motivation (Hwang & Chang, 2011;Hwang & Wu, 2014), as well as on problem-solving skills (Al-Khateeb, 2018;Lai & Hwang, 2014), creativity, and communication skills (Lai & Hwang, 2014).…”
Section: Benefits and Barriersmentioning
confidence: 99%
“…Their collective findings reported that the application of technology in education could improve student anger management skills, enhance the teaching-learning process's effectiveness, increase academic achievement, and foster positive behavior [7][8][9][10][11][12][13]. Other studies presented that the application of technology can raise problem-solving capability, heighten computational thinking competency, upgrade writing ability, be adopted due to usefulness and easiness, and boost motivation [14][15][16][17][18][19]. The advantages of using technology in education in the cognitive and affective domain are seen in the current studies` interests.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, technology usually refers to new devices such as hardware and software [3]. For example, tablets and personal computers with appropriate applications were used to help children's comprehension of numbers [4] and problem solving [5] . Interactive whiteboards and its associated software are installed in the classroom to support the wholeclass mathematics lessons [5].…”
Section: Introductionmentioning
confidence: 99%
“…For example, tablets and personal computers with appropriate applications were used to help children's comprehension of numbers [4] and problem solving [5] . Interactive whiteboards and its associated software are installed in the classroom to support the wholeclass mathematics lessons [5]. Strategic use of technology is recommended to strength the mathematics instruction altogether [6].…”
Section: Introductionmentioning
confidence: 99%